Peripheral and central capillary non-perfusion in diabetic retinopathy: An updated overview - Antropoli, Alessio; Arrigo, Alessandro; La Franca, Lamberto; Bianco, Lorenzo; Barlocci, Eugenio; Fusi, Emanuele; Bandello, Francesco; Battaglia Parodi, Maurizio (Frontiers in Medicine, 2023)
Capillary non-perfusion (CNP) is one of the key hallmarks of diabetic retinopathy (DR), which may develop both in the periphery and at the posterior pole. Our perspectives on CNP have extended with the introduction of optical coherence tomography angiography (OCTA) and ultra-widefield (UWF) imaging, and the clinical consequences of peripheral and macular CNP have been well characterized. Fluorescein angiography (FA) continues to be the gold standard for detecting and measuring CNP, particularly when UWF imaging is available. OCTA, on the other hand, is a quicker, non-invasive approach that allows for a three-dimensional examination of CNP and may soon be regarded an useful alternative to FA. In this review, we provide an updated scenario regarding the characteristics, clinical impact, and management of central and peripheral CNP in DR.